2019
DOI: 10.1051/matecconf/201926602001
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Flooding Impacts to the Built Environment: A Literature Review

Abstract: The paper consists of the literature review and discussions that concerns the built environment, flooding, disaster risk management including resiliency and sustainability theory. The objective of this paper is to review any relevant works of literature in reducing the flooding impacts to the built environment in Malaysia, at the same time describing any potential improvements and current measures to handle the aftermath of flooding. Systematic literature review using reference material such as books, scholarl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Source [49] reported three mitigation measures including: framing good macroeconomic policies, financial plan in crisis, and public investment in hazard reduction. Moreover, other primary mitigations highlighted are good disaster delivery systems by government, the cooperation of government, private sector, non-governmental organization (NGO), and public awareness [50].…”
Section: Flood Disaster Mitigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Source [49] reported three mitigation measures including: framing good macroeconomic policies, financial plan in crisis, and public investment in hazard reduction. Moreover, other primary mitigations highlighted are good disaster delivery systems by government, the cooperation of government, private sector, non-governmental organization (NGO), and public awareness [50].…”
Section: Flood Disaster Mitigationsmentioning
confidence: 99%
“…Moreover, other primary mitigations highlighted are good disaster delivery systems by government, the cooperation of government, private sector, non-governmental organization (NGO), and public awareness [50]. Furthermore, [49] added other mitigation measures to manage flood disasters: flood forecasting, control of flood plan development, catchment management, flood insurance, floodproofing, flood emergency response planning, and emergency assistance and relief. It is also reported that environmental education, hydrological structures, and construction engineering, such as the development of new structures and improving existing water framework efficiency [51].…”
Section: Flood Disaster Mitigationsmentioning
confidence: 99%
“…Capacity building, empowerment and enlightenment Another area of importance to avert flooding in this growing urban centre and also emphasized by Hulah and Udoh ( 20115) is through capacity building and empowerment (especially economic areas) for the inhabitants and other stakeholders in the development of the town especially in the areas exposure to modern ways of carrying out tasks in line with the new technology, improved methods of disposing wastes, waste recycling/reuse, greening of our natural and built-up environment, public facilities maintenance among others. Also, enlightenment on the constitutional roles of citizens to the sustenance of human environment, the significance of environmental harmony among others, should be embraced for attaining disasterfree urban centre (World Bank, 2017;Nurashikin et al, 2019).…”
Section: (4) Appropriate Legislation and Sanctions For The Erring Mem...mentioning
confidence: 99%